DSS1 inhibits autophagy to activate epithelial-mesenchymal transition in a pro-metastatic niche of renal cell carcinoma - Xiaoyu Chen; Qingyuan Liu; Jingxian Wu; Pengfei Zhou; Mingming Zhao; Jing Song (Nature Communications)
Abstract The mechanisms underlying clear cell renal cell carcinoma (ccRCC) metastasis remain largely unexplored. We demonstrate that Deleted in Split hand/Split foot protein 1 (DSS1), a critical cofactor of BRCA2 in DNA repair, is upregulated in metastatic ccRCC and promotes both tumor growth and distant metastasis. Mechanistically, DSS1 interacts with LC3 and promotes its degradation via TRIM25-mediated Lys63 (K63)-linked polyubiquitination at LC3B-K51. This impairs (macro) autophagic flux and leads to p62 accumulation, thereby stabilizing TWIST1 and facilitating its nuclear translocation, ultimately activating epithelial-mesenchymal transition (EMT). DSS1 highly expressed (DSS1hi) tumor cells are enriched in late-stage tumors and are associated with microvascular invasion within a vascularized invasive niche at the tumor-stromal interface, mediated by SPP1-ITGB1 interactions. Clinically, DSS1hi tumor cells correlate with therapeutic resistance and poorer patient outcomes. Collectively, these findings provide new insights into the mechanisms of ccRCC metastasis and suggest potential avenues for therapeutic intervention.